Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1016/j.ydbio.2004.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Transcript profiling during preimplantation mouse development

Abstract: Studies using low-resolution methods to assess gene expression during preimplantation mouse development indicate that changes in gene expression either precede or occur concomitantly with the major morphological transitions, that is, conversion of the oocyte to totipotent 2-cell blastomeres, compaction, and blastocyst formation. Using microarrays, we characterized global changes in gene expression and used Expression Analysis Systematic Explorer (EASE) to identify biological and molecular processes that accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
332
3
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 385 publications
(368 citation statements)
references
References 64 publications
29
332
3
4
Order By: Relevance
“…This was expected since cell cycle and protein degradation through ubiquitin-protesome pathways work coordinately to enable rapid production and degradation of proteins that lead to progression of cell cycle [30]. Similar biological processes were also up-regulated in mouse embryos where mRNAs encoding proteins involved in cell cycle and protein catabolism increased in 2-cell mouse embryos [31]. Contrary to our results, Zeng et al [31] reported significant increase in mRNSs involved RNA processing in 2-cell mouse embryos.…”
Section: Discussioncontrasting
confidence: 71%
“…This was expected since cell cycle and protein degradation through ubiquitin-protesome pathways work coordinately to enable rapid production and degradation of proteins that lead to progression of cell cycle [30]. Similar biological processes were also up-regulated in mouse embryos where mRNAs encoding proteins involved in cell cycle and protein catabolism increased in 2-cell mouse embryos [31]. Contrary to our results, Zeng et al [31] reported significant increase in mRNSs involved RNA processing in 2-cell mouse embryos.…”
Section: Discussioncontrasting
confidence: 71%
“…85 Several lines of evidence support a role for HDAC1 in development of a transcriptionally repressive state that initiates in 2-cell embryos. 42 First, microarray data and qRT-PCR show that Hdac1 is zygotically expressed beginning from 2-cell stage, 42,86,87 accompanying genome activation. Second, HDAC1 protein enters into nucleus in late 2-cell embryos that is concomitant with zygotic genome activation at this stage ( Figure 2).…”
Section: Hdac1 Is the Responsible Hdac Involved In Cell Cyclementioning
confidence: 99%
“…The shorter isoform, which is predicted to encode a truncated protein containing only one MBT domain, results from the use of a polyA site within exon 6. Expression of Sfmbt2 in preimplantation embryos is characteristic of a group of genes with a mid-preimplantation gene activation pattern, when major embryonic expression commences between the 8-cell and blastocyst stage (Fig1C), as assessed from published microarray data (Zeng et al, 2004;Hamatani et al, Dev Cell, 2004). Genes with this expression pattern have been purported to have roles in blastocyst formation and the emergence of distinct cell types in the preimplantaion embryo.…”
Section: Sfmbt2 Is Expressed Robustly In Extraembryonic Tissuesmentioning
confidence: 99%
“…of expression for single androgenetic (n=34), gynogenetic (n=7), and biparental (n=24) blastocysts. Expression data of Sfmbt2 through preimplantation development were compiled from Zeng et al, 2004.…”
Section: Preparation Of Cdna From Uniparental Blastocystsmentioning
confidence: 99%